Examining Millennials' Halal Tourism Intention: The Role of Percieved Halal Risk and Environmental Concern - Muhammad Dzulfaqori Jatnika; Aziz, Nur Jannah Abdi; Alisa, Juniar (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The purpose of this research was to provide a conceptual framework for investigating the effect of perceived halal risk, perceived Islamic value, environmental attitude, environmental concern, and perceived environmental knowledge on intention in visiting halal tourist places in West Java Design/methodology/approach: Purposive sampling was utilized in this study. The study's respondents were 400 Muslim millennials from West Java Province. This study's analytical approach is structural equation modeling-partial least squares (SEM-PLS). The ideas of perceived halal risk and environmental concern were combined to determine how they affect intention in visiting halal tourist hotspots in West Java Research Findings: The study's findings show that perceived halal risk, considered Islamic value, environmental attitude, environmental care, and perceived environmental knowledge all have an impact on visitors' intention both directly and indirectly. Theoretical Contribution/Originality: This paper contributes to filling the gap in the literature related to halal tourism management by combining the concepts of halal risk and TPB. In addition, this paper also uses the enviromental attitude variable as a mediating variable in predicting these two concepts. To the best of the author's knowledge, this research is the first to combine the two concepts and add mediating variables to predict the intention to visit halal tourism destinations.